Treatable traits in the NOVELTY study. Issue 11 (21st July 2022) - Agustí, Alvar; Rapsomaniki, Eleni; Beasley, Richard; Hughes, Rod; Müllerová, Hana; Papi, Alberto; Pavord, Ian D.; van den Berge, Maarten; Faner, Rosa
Abstract: Background and objective: Asthma and chronic obstructive pulmonary disease (COPD) are two prevalent and complex diseases that require personalized management. Although a strategy based on treatable traits (TTs) has been proposed, the prevalence and relationship of TTs to the diagnostic label and disease severity established by the attending physician in a real‐world setting are unknown. We assessed how the presence/absence of specific TTs relate to the diagnosis and severity of 'asthma', 'COPD' or 'asthma + COPD'. Methods: The authors selected 30 frequently occurring TTs from the NOVELTY study cohort (NOVEL observational longiTudinal studY; NCT02760329), a large ( n  = 11, 226), global study that systematically collects data in a real‐world setting, both in primary care clinics and specialized centres, for patients with 'asthma' ( n  = 5932, 52.8%), 'COPD' ( n  = 3898, 34.7%) or both ('asthma + COPD'; n  = 1396, 12.4%). Results: The results indicate that (1) the prevalence of the 30 TTs evaluated varied widely, with a mean ± SD of 4.6 ± 2.6, 5.4 ± 2.6 and 6.4 ± 2.8 TTs/patient in those with 'asthma', 'COPD' and 'asthma + COPD', respectively ( p  < 0.0001); (2) there were no large global geographical variations, but the prevalence of TTs was different in primary versus specialized clinics; (3) several TTs were specific to the diagnosis and severity of disease, but many were not; and (4) both the presence and absence of TTs formed a pattern that is recognized by clinicians to establish a diagnosis and grade its severity. Conclusion: These results provide the largest and most granular characterization of TTs in patients with airway diseases in a real‐world setting to date. Abstract : This study shows which treatable traits are present and/or absent in patients diagnosed with 'asthma', 'COPD' (chronic obstructive pulmonary disease) and 'asthma + COPD' in a global, observational study of more than 11, 000 patients (NOVELTY), and how their prevalence changes with disease severity. See related Editorial